Fabrication of in situ Fe-NbC composite by mechanical alloying - Siti Zalifah Md Rasib; Hussain Zuhailawati (Universiti Kebangsaan Malaysia, 2013)
In this research we investigated the in situ formation mechanism of NbC in mechanically alloyed Fe-Nb-C mixture. Powders of iron, niobium and graphite with a composition Fe-20 %Nb was milled in a planetary mill for various milling times (i.e. 5, 10, 15 and 20 h) to investigate the influence of this variable on phase formation and properties of composite. The mixture was cold pressed and sintered at 1300°C for 1 h. Only phase of the initial raw materials was observed after milling, whilst NbC phase was detected after sintering. Increasing the milling time resulted in an increase in crystallite size and strain energy, which is beneficial for hardness and density improvement.